2021
DOI: 10.1177/02841851211014191
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy of symptomatic isolated occlusions of posterior cerebral arteries in segment P1 and P2 in acute stroke treatment

Abstract: Background Interventional stroke treatments for occlusions of the posterior circulation are established procedures. However, there are limited data on the treatment of isolated symptomatic P1 and P2 occlusions, which we have examined in this study. Purpose To investigate the mechanical thrombectomy of distal posterior occlusions Material and Methods Retrospectively, data from patients with isolated P1 and P2 occlusions treated with MT were evaluated. Successful reperfusions have been defined as modified thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…[ 13 ] 2021 Portugal Single-center retrospective cohort 38 P1 ( n = 19), P2 ( n = 16), P3 ( n = 3) 25 79.3 (±2.4) 16/9 10 (6.0–14.5) 14 (56%) Stent retriever; aspiration thrombectomy; intra-arterial thrombolysis 13 75.3 (±3.93) 7/6 8 (5.5–10.0) 13 (100%) Altenbernd et al. [ 14 ] 2021 Germany Single-center retrospective cohort 79 P1 ( n = 60), P2 ( n = 19) 79 72.8 (±11.6) 35/44 12 (4–15) 43 (54%) Stent retriever; aspiration thrombectomy Herweh et al. [ 15 ] 2021 Germany, USA, Taiwan Multicenter retrospective cohort 130 P1 ( n = 62), distal to P1 ( n = 68) 23 70 (±13.3) 14/9 9 (1–20) a 5 (22%) Mechanical thrombectomy 107 74 (±13.1) 56/51 7 (1–38) a 44 (41%) Meyer et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] 2021 Portugal Single-center retrospective cohort 38 P1 ( n = 19), P2 ( n = 16), P3 ( n = 3) 25 79.3 (±2.4) 16/9 10 (6.0–14.5) 14 (56%) Stent retriever; aspiration thrombectomy; intra-arterial thrombolysis 13 75.3 (±3.93) 7/6 8 (5.5–10.0) 13 (100%) Altenbernd et al. [ 14 ] 2021 Germany Single-center retrospective cohort 79 P1 ( n = 60), P2 ( n = 19) 79 72.8 (±11.6) 35/44 12 (4–15) 43 (54%) Stent retriever; aspiration thrombectomy Herweh et al. [ 15 ] 2021 Germany, USA, Taiwan Multicenter retrospective cohort 130 P1 ( n = 62), distal to P1 ( n = 68) 23 70 (±13.3) 14/9 9 (1–20) a 5 (22%) Mechanical thrombectomy 107 74 (±13.1) 56/51 7 (1–38) a 44 (41%) Meyer et al.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent similar meta-analysis on this subject also found no differences in favorable 3‑month outcome, 3‑month mortality or sICH [ 26 ]. This meta-analysis had different search criteria, did not include six relevant studies which we identified in our search [ 9 , 11 , 14 , 17 , 21 , 22 ], therefore including only 338 iPCA patients who underwent EVT (compared to 461 patients in our study), and did not report relevant outcomes such as excellent 3‑month outcome, NIHSS change or improvement of visual field defects. This meta-analysis [ 26 ] performed comparisons of EVT versus best medical treatment in the same four studies but used the non-matched patient population of one of the studies [ 16 ], which is a potential source of relevant bias.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Unilateral CN III palsy is an atypical presentation of P1 segment thrombosis. 5 Usually, patients with P1 ischemic stroke present with hemiparesis, sensory loss, and visual problems, 6,7 as P1 perforating branches supply cerebral peduncles, tegmentum, and geniculate bodies, colliculi, and pulvinar of thalamus. 8 Blood supplies of the proximal part of the third cranial nerve could explain CN III palsy following an isolated P1 segment.…”
Section: A B Cmentioning
confidence: 99%